الدبيلة الصدرية: أسباب، تشخيص وتقييم الطرق المختلفة في العلاج - رومية, دمر أحمد (Latakia University Journal -Medical Sciences Series, 2019)
The main aim of our study is to analyze the different therapeutical methods in the treatment of thoracic empyema and its results as well. medical files of (136) patients with thoracic empyema were analyzed. 77.2% of those patients were males. The ages of our patients were ranging between (16-78) years. 62.5% of our patients were younger than 40 years. right side of the chest was mostly affected 58% of the patients. Non specific pneumonia was the leading and the most important factor causing thoracic empyema accounting 71.3%. The second cause was warfare thoracic injuries accounting 15.4%, whereas the tuberculous infection had the third cause accounting 6.6%. 51.4% of the patients categorized in the third stage of thoracic empyema. CXR was performed for all patients, whereas the chest CT-Scan was done by 91.1% of the patients. Chest ultrasound was done only by 8.8% of the patients. Thora centesis was considered only as a diagnostic procedure and not as a therapeutic one and was done by 48.5% of the patients. The success rate of thoracic drainage in the treatment of the first stage was 66.6%, whereas the success rate of VATS was 100%. In the treatment of the second stage 3 kinds of procedures were employed: Thoracic drainage, VATS and open Thoracotomy with success rate 40%, 86.6%, and 100% perspectively. Hospital stay was longer when the patients were treated with thoracic drainage in the first stage (13) days and (14) days in the second stage. The application of VATS Technique in the treatment of thoracic empyema has greatly decreased the length of hospital stay in the first stage (5) days and also in the second stage (6) days. Complications occurred in 13.9% of the patients, and fortunately all these complications were simple and treated conservatively. Mortality rate was 2.9% of the cases within one month after surgical procedure. إن الهدف الرئيسي من هذه الدراسة هو دراسة الطرائق العلاجية المختلفة لحالات الدبيلة الصدرية في مختلف مراحلها ودراسة نتائج العلاج. تمت دراسة الملفات الطبية ل (136) مريضاً مصاباً بالدبيلة الصدرية. %77.2 من هؤلاء المرضى كانوا ذكوراً، تراوحت أعمار المرضى بين (16 – 78) عاماً. %62.5 من هؤلاء المرضى كانوا بأعمار أقل من (40) عاماً. الجهة اليمنى كانت مصابة عند %58 من المرضى. إنتانات الرئة غير نوعية كانت السبب الأول والأهم في حدوث الدبيلة الصدرية بنسبة %71.3 بينما احتلت الإصابات الحربية المركز الثاني بنسبة %15.4 والإصابات السليّة المركز الثالث بنسبة %6.6. %51.4 من المرضى كانوا ضمن المرحلة الثالثة من الدبيلة الصدرية. أجريت صورة الصدر البسيطة عند كل المرضى بينما أجري التصوير الطبقي المحوري للصدر لدى %91.1 , الإيكو أجري لدى %8.8 من المرضى فقط. اعتبر بزل الجنب في دراستنا كوسيلة تشخيص فقط وأجري لدى %48.5 من المرضى ولم نقم به كطريقة علاجية لدى أي من مرضانا. بلغت نسبة نجاح وضع مفجر الصدر كطريقة علاجية في المرحلة الأولى %66.6 بينما كانت نسبة نجاح VATS 100%. في علاج المرحلة الثانية طبقت ثلاث طرق علاجية هي وضع مفجر الصدر بنسبة نجاح 40%، VATS بنسبة نجاح 86,6% وفتح الصدر بنسبة نجاح 100%. فتح الصدر التقليدي أجري لكل مرضى المرحلة الثالثة بنسبة نجاح 100%. مدة البقاء في المشفى كانت أعلى عند المرضى المعالجين بوضع مفجر الصدر في المرحلة الأولى حيث بلغت (13) يوما وفي المرحلة الثانية (14) يوما. أما تطبيق تقنية VATS فقد أنقص وقلل هذه الفترة بشكل كبير حيث بلغت في المرحلة الأولى (5) أيام وفي المرحلة الثانية (6) أيام. حدثت المضاعفات في 13,9 % من المرضى وكانت كلها مضاعفات بسيطة تمت السيطرة عليها بطرق محافظة. الوفيات حدثت بنسبة 2,9 % من الحالات خلال شهر من العلاج الجراحي.